2010
DOI: 10.1371/journal.pone.0008545
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Reliability of Pallor for Detecting Anaemia: A Hospital-Based Diagnostic Accuracy Study

Abstract: BackgroundAnaemia is a common disorder. Most health providers in resource poor settings rely on physical signs to diagnose anaemia. We aimed to determine the diagnostic accuracy of pallor for anaemia by using haemoglobin as the reference standard.Methodology/Principal FindingsIn May 2007, we enrolled consecutive patients over 12 years of age, able to consent and willing to participate and who had a haemoglobin measurement taken within a day of assessment of clinical pallor from outpatient and medicine inpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 18 publications
3
30
0
1
Order By: Relevance
“…[2] A separate study suggested tongue pallor for ruling in severe anemia instead of palmar crease pallor. [18] The results were quite similar to our study as our study suggested that absence of palmar crease pallor does not rule out severe anemia and severe tongue pallor has highest sensitivity for severe anemia (88%). Another study revealed that different pallor sites including conjunctiva, nail-bed and palm were equally useful for detecting severe anemia, however palmar creases were not mentioned specifi cally.…”
Section: Discussionsupporting
confidence: 90%
“…[2] A separate study suggested tongue pallor for ruling in severe anemia instead of palmar crease pallor. [18] The results were quite similar to our study as our study suggested that absence of palmar crease pallor does not rule out severe anemia and severe tongue pallor has highest sensitivity for severe anemia (88%). Another study revealed that different pallor sites including conjunctiva, nail-bed and palm were equally useful for detecting severe anemia, however palmar creases were not mentioned specifi cally.…”
Section: Discussionsupporting
confidence: 90%
“…16,19,48 Although conjunctival pallor is valuable information as a clinical sign for severe anemia, it cannot provide reliable diagnosis in clinical settings. Further, quantification of Hgb from conjunctival pallor using digital photography has received attention.…”
Section: Limitations Of Conventional Rgb-based Photometric Technologiesmentioning
confidence: 99%
“…12,13 Indeed, optical assessment of the inner eyelid has received attention in anemic patients for assessing Hgb content from human individuals, which could be highly correlated with a lab-based blood Hgb test. [14][15][16][17][18][19] For accurate and precise Hgb measurements, typical spectroscopic technologies heavily rely on the use of spectrometers, spectrographs, and liquid tunable crystal filters. 20,21 However, these critical optical components for highly accurate and sensitive Hgb measurements significantly limit the development of compact, portable, and cost-effective devices.…”
Section: Introductionmentioning
confidence: 99%
“…Kalantri et al have documented that physical estimation of pallor for detection of anaemia strongly correlates with laboratory estimation of haemoglobin. [20] JMSCR Vol||06||Issue||03||Page 1170-1174||March 2018…”
Section: Discussionmentioning
confidence: 99%